ANALISIS KONTEKS WACANA DALAM CERPEN “KULI KONTRAK” KARYA MOCHTAR LUBIS - Melati, Felisitas Victoria; Pranowo, Pranowo (Universitas Hamzanwadi, 2022)
This study aims to describe the context of literary discourse in the short story Kuli Kontrak by Mochtar Lubis. This research study focuses on the context behind the short story Kuli Kontak by Mochtar Lubis. This research uses descriptive qualitative research. This research uses the literature study method, the source of the data for this research is the Kuli Kontak short story book, the data is obtained from the sentences contained in the short story. The results of this study found that there are linguistic contexts, situational contexts, and cultural contexts which are the building blocks of Mochtar Lubis' short stories.